Hubungan Budaya Disiplin Organisasi Dengan Kinerja Pegawai Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Pangkep - Rusdi, Rusdi; Malik, Ihyani; Mustari, Nuryanti (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purposed of this study was to find out the relationship between organizational discipline culture and employee performance in the population and civil registration offices in Pangkep Regency. This study used mixed method research. Data collection used observation and questionnaires, interviews with a number of informants were the Head of Population and Civil Registration Office of Pangkep Regency and the head of the subdivision, data analysis technique used simple correlation. Data were analyzed by simple regression with SPSS 16.0 for Windows software. The results showed that the relationship between organizational culture and employee performance was effective in a culture of time discipline, employees had arrived punctual, the rules set by the agency, employees had obeyed these regulations, and their responsibilities the responsibility that the employees was good. Employees 'job descriptions were structured well, but the completion of their duties was still not on time and job placements were in accordance with the employees' abilities. Keywords: Culture, discipline, performance, employees.